Associations of + 138 Ins/del A and + 5665 G/T polymorphisms of endothelin-1 gene with hypertension in Burmese people in Magway, Myanmar - Win Min Oo; Kyaw Thiha; Myat Mon Khine (BMC, 2022)
Abstract Background Hypertension is one of the major public health problems worldwide, and is one of the recognized causes of premature deaths every year in the world. The purpose of this study was to investigate the associations between the + 138 insertion/deletion of adenine (Ins/del A) and + 5665 guanine-to-thymine (G/T) polymorphisms of the endothelin-1 gene and hypertension in the residents of Magway Township, Myanmar. Methods This study was a cross-sectional comparative study including 60 hypertensive patients and 60 control subjects in Magway Township, Myanmar. The inclusion criterion for hypertension was blood pressure ≥ 140/90 mmHg or previous diagnosis by a physician as hypertension and/or taking antihypertensive drugs. The control group had blood pressure < 140/90 mmHg and no previous diagnosis of hypertension. The genotyping was done by polymerase chain reaction and restriction fragment length polymorphism method. Results In this study, the genotype distribution of the + 138 Ins/del A variant was significantly different between hypertensive patients and the control group, especially in the 3A4A genotype (odds ratio [OR], 2.451; 95% confidence interval [CI], 1.138-5.280; P = 0.022). Adenine insertion genotypes (3A4A and 4A4A) were significantly associated with hypertension in the dominant model (OR, 2.494; 95% CI, 1.179-5.276; P = 0.017). In addition, there was a significant association between the 4A allele and hypertension (OR, 1.771; 95% CI, 1.026-3.056; P = 0.040). The genotype and allelic distributions of the + 5665 G/T polymorphism were not significantly different between the hypertensive patients and the control group (P > 0.05). In this study, there was no significant association between the genotype and allele frequency, and hypertension (P > 0.05). The linkage disequilibrium was weak between the + 138 Ins/del A and + 5665 G/T loci (D' = 0.108, r2 = 0.009). Conclusions This study provides evidence that the + 138 Ins/del A rather than + 5665 G/T polymorphism is associated with hypertension in Burmese people.